SURGICAL CORRECTION OF BLEPHAROPTOSIS IN THE ELDERLY PATIENTS - Jarullazada, I.Ch.; Jarullazada, Ch.D. (World of Medicine and Biology, 2025)
The demographic trends of the planet are such that with an increase in life expectancy, the older population will almost double from 2005 to 2050. Ensuring a decent quality of life for older people is one of the main tasks of a developed social society. Against the background of the natural aging process of the body, changes in the form of involutional (senile) blepharoptosis and concomitant age-related changes in the periorbital region deserve attention. This study aimed to determine the optimal tactics of upper eyelid ptosis surgery from the perspective of a comprehensive assessment of concomitant age-related changes such as overhanging folds of the upper eyelid, fat packs of the lower eyelids, as well as lowering of the eyebrows to achieve a cosmetically acceptable result for the patient. The choice of blepharoptosis correction tactics should be considered from the standpoint of a one-time elimination of age-related changes, the correction of which can ensure both functional and cosmetic satisfaction of the patient.